ЭФФЕКТИВНЫЙ СПОСОБ ПОСТРОЕНИЯ ИНТЕРПОЛЯЦИОННОГО КУБИЧЕСКОГО СПЛАЙНА - Отаров, А.О.; Таджиев, Т.М. (SCIENCE and SOCIETY, 2020)
The article provides an effective ways of building an interpolar cubic spline. Formulas are derived that express of the spline coefficient through its moments. The problem of determining the moments of a spline is reduced to solving a system of linear algebraic equations with a tridiagonal matrix. It always has a unique solution and it can be effectively solved by the run method, which is stable with relative calculation errors.